EFEKTIVITAS PENGGUNAAN INFOGRAFIS ALUR DALAM PENYAMPAIAN INFORMASI - Widya sari; Aditya Rahman Yani; Aileena Solicitor Costa Rica El-Chidtian (Gestalt : Jurnal Desain Komunikasi Visual, 2019)
In this modern era, there has been a need for practical and interesting information to the public. Likewise, UPN "Veteran" Jawa Timur continues to improve the model of information delivery from Standard Operating Procedures (SOPs) in its academic service system. This research was conducted to find a solution in creating a model of delivering that information using visual infographic style. Visual infographic style can combine information with design that can help individuals and organizations communicate briefly and clearly to the audience. The type of infographic used is the type of infographic that explains the flow in stages in various models will be measured their level of effectiveness. The research method used is qualitative and quantitative methods, namely by conducting literature studies, interviews and observations. The data obtained will be analyzed using the TOWS Matrix, an analysis of the target audience's insights using the why test method, the preparation of the questionnaire, and the inference of the results of the questionnaire. Through this infographic media, it is expected that information about SOPs in the academic service system can be conveyed clearly and easily understood by UPN "Veteran" Jawa Timur students.